Architectural fragments in the Jain temple complex - Temples of India Project Team (Jio Institute, 2024)
Seen here are the scattered architectural fragments in the Jain temple complex consisting of several architectural members along with a Jina sculpture seated in padmasana (lotus pedestal). It is likely that all these architectural and sculptural remains originally formed part of the Jain temple complex. Since the central shrine of the Jain temple is well preserved, the fragments of the wall with floral ornamentation might have been part of the side shrines in this complex.